The acute effects of music therapy on neonates in a Neonatal Intensive Care Unit (Research, Society and Development, 2024)
Objectives: To evaluate the acute effects of music therapy (MT) on cardiorespiratory monitoring, stressors, and pain in Neonatal Intensive Care Unit (UTIN). Methodology: This was a randomized, controlled, descriptive and quantitative clinical trial carried out in a UTIN. Nineteen neonates took part: 9 in the control group (CG) and 10 in the experimental group (EG). Neonates were included after 72 hours until the 28th day of life, both sexes, gestational age over 28 weeks and more than 1.5 kg. A clinical assessment was carried out using the assessment form. The EG underwent the MT protocol for 20 minutes. Heart rate (HR), breathing rate (BR) and peripheral saturation (SpO2) were assessed, as well as the Neonatal Infant Pain Scale (NIPS) and Behavioral Indicators of Infant Pain (BIIP), before, during and after the intervention. SPSS® was used for statistical analysis. Results: Most of the sample was made up of male neonates (SG 60% - CG 55.6%) and premature infants (average of 35 weeks). The MT protocol did not cause differences between groups or within groups, however, there was a tendency for a more reduction in the EG: HR before and after (150.60 ± 16.58 vs 139.80 ± 19.11); BR before and during (44.8 ± 16.84 vs 39.10 ± 19.77); NIPS and BIIP before, during and after (1.5± 2.67 vs 0.7±1.88 vs 07±1.88) and (1.5±2.91 vs 0.8±2.20 and 0.9±2.51). Final Considerations: Despite the small sample size, this study suggests positive results in the relaxation of internal neonates with a standardized music therapy protocol.